Involvement of Notaries Who Commit Unlawful Acts in Making Deeds of General Meeting of Shareholders and Its Legal Consequences (Case Study of Supreme Court Decision Number 2826 K/Pdt/2021) - Wulandari, Dewi; Gunadi, Ariawan (Dinasti Research, 2024)
The RUPS is the highest forum for making company decisions for the benefit of various parties, where shareholders have the opportunity to express opinions, vote, and make decisions regarding company policies. In the GMS, a notary plays a role in making the minutes of the GMS, which records and formulates the entire course of the GMS containing all decisions taken during the meeting, including the results of voting and discussion. The minutes must be signed by the notary and the chairperson of the meeting for legal certainty. In addition, the notary is responsible for ensuring that the GMS is conducted in accordance with applicable regulations, both in terms of form and substance. The notary must verify the validity of the meeting invitation, quorum, and voting rights of the shareholders. However, notaries are often negligent in performing their duties and authorities, which can be categorized as unlawful acts. This research is intended to analyze unlawful acts committed by notaries and the legal consequences arising therein for companies through Supreme Court Decision Number 2826 K/Pdt/2021, using normative juridical methods. The results showed that the unlawful act committed by the notary through the decision was negligence in verifying the results of the GMS due to the absence of the notary in the quorum. This resulted in the actions of a person who served as Director and President Director whose appointment was invalid. This made the notary involved as a defendant in the case and subject to civil sanctions.